(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The formation of the structure of equity in many private enterprises is carried out intuitively, or according to tradition, without proper analytical and mathematical justification. In this situation, the importance of managing your own equity rises sharply. The financial well-being of the enterprise as a whole, its owners and employees, depends on how efficiently and appropriately it is transformed into fixed and current assets. Improving the effectiveness of entrepreneurial activity ensures the growth of the economic potential of the state and vice versa - the emergence of crisis phenomena at individual enterprises negatively affects the economic system as a whole. Under such conditions, the enterprise itself should become the center of further economic reforms in order to create a functionally effective, strategically oriented and democratic economy.